Annual groundwater recharge estimation in Nineveh plain, northern Iraq using Chloride Mass Balance (CMB) method - Fatima AJ. Abdul Wahab; Alaa M. Al-Abadi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This study evaluates groundwater recharge in the Nineveh Plain, northern Iraq, using the Chloride Mass Balance (CMB) method. The CMB method estimates recharge based on the conservation of chloride mass, relying on the comparison of chloride concentrations in precipitation and groundwater. Recharge rates calculated using this method ranged from 0.22 to 2.54 cm/year, with higher values observed in the northern regions due to greater precipitation and favourable infiltration conditions. Validation of the CMB-derived recharge map against hydrological parameters, such as the Curve Number (CN), yielded a strong correlation coefficient of 0.71, affirming the reliability of this method for estimating recharge.